2022
DOI: 10.3390/tropicalmed7110338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features Related to Severity and Mortality among COVID-19 Patients in a Pre-Vaccine Period in Luanda, Angola

Abstract: Background: Infection due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with clinical features of diverse severity. Few studies investigated the severity and mortality predictors of coronavirus disease 2019 (COVID-19) in Africa. Herein, we investigated the clinical features of severity and mortality among COVID-19 patients in Luanda, Angola. Methods: This multicenter cohort study involved 101 COVID-19 patients, between December 2020 and April 2021, with clinical and laboratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies have documented higher rates of STIs and other communicable diseases in Luanda, partly due to the high concentration of risk groups such as sex workers and injecting drug users. [28][29][30][31][32][33] Likewise, studies carried out in Ethiopia and Pakistan also showed that the majority of blood donation candidates with positive serology came from urbanized regions. [34,35] Although not statistically signi cant (p > 0.05), more than 95% of STI and 100% of multiple infections were observed in unmarried subjects, indicating that this group may serve as a potential source of STI dissemination (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented higher rates of STIs and other communicable diseases in Luanda, partly due to the high concentration of risk groups such as sex workers and injecting drug users. [28][29][30][31][32][33] Likewise, studies carried out in Ethiopia and Pakistan also showed that the majority of blood donation candidates with positive serology came from urbanized regions. [34,35] Although not statistically signi cant (p > 0.05), more than 95% of STI and 100% of multiple infections were observed in unmarried subjects, indicating that this group may serve as a potential source of STI dissemination (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, Africa accounted for only 12.8 M cases and 259,000 reported deaths 1 . These reports were likely vastly underestimated as significant excess mortalities were reported throughout Africa 2,3 . A high estimated incidence of asymptomatic infections and limited testing in many regions 4 support the notion that many case numbers remain undocumented 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 To understand the impact of COVID-19 in Angola, some studies reported putative factors related to morbidity, severity, and mortality due to COVID-19, including age over 40 years, symptoms such as cough, fever, gastrointestinal symptoms, and asthenia, as well as comorbidities such as hypertension, diabetes mellitus, and chronic kidney disease. 4 Since there are few studies conducted in African countries, we proposed to study clinical characteristics and variables associated with COVID-19 in a tertiary-level hospital in Luanda, the capital city of Angola, during the first year of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%